Urban Heat Island dan Vegetasi: Analisis Spasial Indeks NDVI, NDMI, dan NDBI - Gilberto Jemali; Wiwin Sulistyo (Simetris: Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2026)
This evaluates land cover changes and their impact on surface temperature dynamics in Bekasi City using Landsat 8 imagery from 2013 and 2023 through NDVI, NDMI, NDBI, and LST indicators. The approach integrates multispectral analysis with spatial autocorrelation analysis (Moran’s I) to examine Urban Heat Island (UHI) patterns. The results show a decrease in NDVI from 0.172 to 0.152 and NDMI from 0.064 to 0.042, indicating a reduction in vegetation and surface moisture. Conversely, NDBI increased from 0.198 to 0.244, accompanied by a rise in surface temperature from 40.1°C to 43.3°C and the expansion of heat-prone areas toward the eastern and southern regions. The decline in Moran’s I from 0.394 to 0.304 reflects a more dispersed heat distribution pattern. Correlation analysis reveals negative relationships between NDVI–LST and NDMI–LST, while NDBI–LST shows a positive correlation. This study highlights the crucial role of vegetation in mitigating UHI and contributes by integrating spectral indices with spatial-temporal analysis to support more effective planning of Green Open Spaces (RTH)